Modeling Political Discourse in Indonesia’s 2024 Election Using Unsupervised Machine Learning - Malikhatul Ibriza; Maya Rini Handayani; Wenty Dwi Yuniarti; Khothibul Umam (ISB Atma Luhur, 2025)
The 2024 General Election in Indonesia has generated a large volume of diverse and unstructured digital political discourse, necessitating a machine learning-based analytical approach for efficient, objective, and scalable data processing. This study aims to map political discourse from 14,813 text data collected from the open-source